THE EFFECT OF BREED, b-LACTOGLOBULIN VARIANTS AND SOMATIC CELL COUNT ON YIELD, CHEMICAL COMPONENTS AND WHEY PROTEIN COMPOSITION IN MILK OF NON-DAIRY SHEEP - A. Rozbicka-Wieczorek; A. Radzik-Rant; W. Rant; K. Puppel (Journal of Animal and Plant Sciences, 2015)
The number of studies regarding the influence of genetic and environmental factors of ovine milk properties of non-dairy breeds is limited. The aim of this study was to determine the influence of breed, b-lactoglobulin variants and somatic cell count on the content of the principal milk ingredients and whey protein components. The study was carried out on 60 Polish Lowland and Polish Heath ewes, which come from the same flock and were kept under the same management and feeding practise. Both these breeds did not differ in respect of the principal components of milk. The milk of the Lowland sheep was characterized by a higher b-lactoglobulin/a-lactalbumin ratio compared to milk of Polish Heath breed.  The b-lactoglobulin variants have affected the content of casein and lactose, which was higher in the milk of ewes with the BB genotype. The increase in somatic cell count decreased total protein, casein and b-lactoglobulin, and significantly increased the share of lactoferrin. The b-lactoglobulin variants and somatic cell count mainly affected the components of the protein fraction of milk.
Keywords: sheep; milk ingredients; whey proteins; somatic cell count